In-situ transesterification of Jatropha curcas L. seeds using homogeneous and heterogeneous basic catalysts. (1st January 2019) - Martínez, Araceli; Mijangos, Gabriela E.; Romero-Ibarra, Issis C.; Hernández-Altamirano, Raúl; Mena-Cervantes, Violeta Y.
Abstract: The in-situ or direct transesterification from non-edible Jatropha curcas L. (Jatropha) seeds is a suitable alternative to produce fatty acid methyl esters (FAME) in one-step. The FAME production was investigated in presence of homogeneous (NaOH) or heterogeneous (Na2 ZrO3 ) catalysts. Parameters, such as catalyst concentration (between 1 and 10 wt%), reaction time, temperature and methanol/oil molar ratio were analysed. The maximum heterogeneous direct transesterification of FAME yield was 99.9% using 5 wt% of Na2 ZrO3 at 65 °C and 8 h. Results showed that no solvent for oil extraction is required. The resulting FAME shows good purity and composition. Moreover, no water is required to purify the FAME. Compositional analysis of FAME indicated that linoleic (C18:2), oleic (C18:1) and palmitic (C16:0) methyl esters were the major components. In addition, the reusability of the catalyst was also investigated. The basic heterogeneous catalyst exhibited stability in the direct transesterification reactions with yields of  >72.5% during five cycles. Finally, Green Metrics values were proposed as parameters to evaluate the FAME obtained in one-pot from seeds directly. The heterogeneous direct transesterification process resulted 55% greener as compared to conventional transesterification and 39.4% greener than homogenous direct transesterification. Heterogeneous direct transesterification is a promising alternative for more clean, efficient, scalable and cost-effective FAME production that has the potential to developing new technologies.